Multiphysics design and optimization of a vibration-based energy harvester from pantograph-catenary interaction. Issue 1 (September 2020) - Genovese, A; Schiano, S; Strano, S; Terzo, M; Iodice, M; Indolfi, M; Coppola, G
Abstract: In this paper, the design of a vibration-based energy harvester mounted on the railway pantograph is discussed. The system aims to feed the diagnostic system of the pantograph-catenary interaction by recovering energy from the vibrations of the pantograph head itself. The design of the system is developed through a multiphysics finite element model, parametrized by means of experimental tests. The performance of the optimized solution, in terms of generated power, highlights the affability of the proposed solution.